Aqueous ammonia and amino acid salts blends for CO2 capture - Yang, N.; Xu, D.; Yang, Q.; Wardhaugh, L.; Feron, P.; Li, K.; Tade, Moses; Yu, J.; Wang, S.; Yu, H. (International Pittsburgh Coal Conference, 2013)
Aqueous ammonia (NH3) is considered as a promising alternative to amine based absorbents for CO2 absorption. However, aqueous ammonia has low absorption rate for CO2 capture and ammonia itself is volatile. To enhance CO2 absorption rate in aqueous ammonia, a number of amino acid salts were investigated as the potential promoter due to their high reaction rates with CO2 and lower vapour pressure. According to pKa values of amino acids and screening test results of amino acid salts in the presence and absence of ammonia, potassium salts of sarcosine, proline and taurine were selected for further study in this work. It has been found that the overall gas phase mass transfer coefficients of CO2 in ammonia blended with amino acid salts are much higher than those in ammonia alone. However, ammonia loss increases with introduction of amino acid salts.